Persepsi Media Massa dalam Kasus Pencabutan ID Pers Jurnalis CNN di Istana Negara Berdasarkan Undang-Undang Pers - Uswatun Nur Auliya; Intan Dyah Ayu Apriani; Raihani Khairunissa Barni; Evi Satispi; Tria Patrianti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study analyzes media perceptions of the revocation of CNN Indonesia journalists' press identity cards by the State Palace in 2025, using the legal framework of Law Number 40 of 1999 concerning the Press. The main objective of the study is to examine the extent to which provisions in the Press Law function effectively in providing legal protection for journalists, as well as to identify potential restrictions on statements deemed inappropriate for public access by the Palace. The method used is qualitative with a descriptive-analytical approach, combining literature review, legal document analysis, and review of national media coverage. The research findings indicate that the revocation of Press IDs without going through the Press Council mechanism contradicts the principles of due process and press freedom guaranteed in the Press Law. This incident created a critical perception that the government has the potential to restrict journalists' freedom, especially regarding strategic state policy issues. Informal resolution through mediation and official apologies do not change the reality that the implementation of non-litigation mechanisms in the Press Law is crucial. This study concludes that the role of the Press Law in protecting the journalistic profession is highly dependent on the government's commitment to guaranteeing press freedom, information transparency, and strengthening the media as a pillar of democracy.